Exploring Local People’s Perception of Ecosystem Services in Djoumouna Periurban Forest, Brazzaville, Congo - V. Kimpouni; J. D. D. Nzila; N. Watha-Ndoudy; M. I. Madzella-Mbiemo; S. Yallo Mouhamed; J.-P. Kampe (International Journal of Forestry Research)
The perception of ecosystem goods and services by local residents is studied in Brazzaville, around the periurban forest of Djoumouna. This study, which documents the ecosystem services provided to communities by this ecosystem facing anthropogenic degradation, evaluates the understanding and consideration of these functions, according to socioprofessional categories. Socioeconomic and ethnobotanical surveys conducted among the group of informants are supported by direct field observations and literature review. The data collected within a 2 km radius around the forest were subjected to descriptive and statistical analysis. The group of informants, including all socioprofessional strata, was organised into 4 age groups and involved 143 heads of household aged from 15 to over 45. The survey reveals 14 ecosystem services that fall into three categories. The provisioning services included food, wood energy, pharmacopoeia, and wood services. The regulatory functions cited are maintaining air quality, shade, erosion control, and windbreak. Recognized sociocultural services are the source of income, recreation, and ecotourism, source of inspiration, fishing, initiation sanctuary, and hunting. According to gender, men are more dependent on the forest than women, and those aged 15–25 and over 45 are the most active. The socioprofessional scale shows an unequal exploitation of the forest. The informants, at least for the majority, integrate the notions of the value of ecosystem services, provided by the Djoumouna periurban forest, into their daily lives. Finally, the study highlights the social and ecological value of periurban and urban forests in the daily lives of people and urban resilience.